Readers' theatre competition 2014 - Ch'ng, Looi Chin (Universiti Teknologi MARA, Sarawak, 2015)
The main aim of this activity was to cultivate the reading habit among the undergraduates as reading is one of the keys to enhance language learning as well as to improve their academic performance.